2011
DOI: 10.1097/inf.0b013e3182218656
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Incidence of Influenza A But Not Influenza B Associated With Use of Hand Sanitizer and Cough Hygiene in Schools

Abstract: Background Laboratory-based evidence is lacking regarding the efficacy of non-pharmaceutical interventions such as alcohol-based hand sanitizer and respiratory hygiene to reduce the spread of influenza. Methods The Pittsburgh Influenza Prevention Project was a cluster-randomized trial conducted in ten Pittsburgh, PA elementary schools during the 2007-2008 influenza season. Children in five intervention schools received training in hand and respiratory hygiene, and were provided and encouraged to use hand san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 23 publications
(21 reference statements)
2
89
0
1
Order By: Relevance
“…In the same two cluster randomised studies in schools reported above, 12,13 hand hygiene interventions were In subgroup analysis in one study, there was a significantly lower incidence of influenza A in the intervention group: adjusted IRR = 0AE48 (95% CI 0AE26-0AE87) but not for influenza B: adjusted IRR = 1AE45 (95% CI 0AE79-2AE67). Outcome rated 'moderate quality' due to serious risk of bias associated with low rates of influenza testing which may have been differential across intervention and control groups: in one study, only 34% of school absences had a reason given (so many ILIs may have been missed) and up to 24% of ILIs identified were not tested for influenza.…”
Section: Hand Hygiene and Influenza-like Illness Or Acute Respiratorymentioning
confidence: 83%
See 2 more Smart Citations
“…In the same two cluster randomised studies in schools reported above, 12,13 hand hygiene interventions were In subgroup analysis in one study, there was a significantly lower incidence of influenza A in the intervention group: adjusted IRR = 0AE48 (95% CI 0AE26-0AE87) but not for influenza B: adjusted IRR = 1AE45 (95% CI 0AE79-2AE67). Outcome rated 'moderate quality' due to serious risk of bias associated with low rates of influenza testing which may have been differential across intervention and control groups: in one study, only 34% of school absences had a reason given (so many ILIs may have been missed) and up to 24% of ILIs identified were not tested for influenza.…”
Section: Hand Hygiene and Influenza-like Illness Or Acute Respiratorymentioning
confidence: 83%
“…Outcome rated 'moderate quality' due to serious risk of bias associated with low rates of influenza testing which may have been differential across intervention and control groups: in one study, only 34% of school absences had a reason given (so many ILIs may have been missed) and up to 24% of ILIs identified were not tested for influenza. 12 In a second study, only 33%…”
Section: Hand Hygiene and Influenza-like Illness Or Acute Respiratorymentioning
confidence: 92%
See 1 more Smart Citation
“…Remarkably, the incidences of vomiting/nausea and diarrhea in our series were significantly higher in pediatric patients as compared to their adult counterpart (Table 1). It is unknown whether or not the higher incidences of vomiting/nausea and diarrhea in pediatric patients resulted from the higher burden of the 2009 pandemic influenza A (H1N1) virus in the affected children, 26 higher chances of exposure to the crowding environments at school, 28 , 29 and/or poorer compliance to the widely advised hand hygiene in the 2009 influenza A (H1N1) epidemic 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Centers for Disease Control and Prevention cited "avoid touching your eyes, nose, or mouth" as a behavior to further prevent influenza infection in the home, school and workplace 4) . In a school setting, Stebbins S, et al studied the efficacy of nonpharmaceutical intervention including the recommendation to "avoid touching your eyes, nose, or mouth" to reduce the spread of influenza 5) . To the extent known, however, no studies appear to have epidemiologically studied the practice of touching the eyes or nose and susceptibility to URTI (including influenza) in workers.…”
Section: Discussionmentioning
confidence: 99%